Knowledge management and its relationship to self-efficacy among graduate students (Journal of the College of Basic Education, 2026)
It aims to study the relationship between knowledge management and self-efficacy among graduate students, and also seeks to identify statistically significant differences between these two variables according to variables such as gender and specialization. 200 male and female graduate students were selected using a random method. The researcher used two scales: the first to measure knowledge management (20 paragraphs), and the second to measure self-efficacy (40 paragraphs). The validity and reliability of the tool were verified, and appropriate statistical methods were used to analyze the data. The results showed that graduate students enjoy a good level of knowledge management and self-efficacy, with no statistically significant differences between the variables studied (gender and specialization). The results also showed a direct relationship between knowledge management and self-efficacy. The research concluded with a number of recommendations and proposals.